Hydrometeorological network interconnectivity in Chimborazo Province, Ecuador - Ayala, Johanna E.; Recalde, Celso G.; Sanaguano, Daniel A. (Rev. Téc. Fac. Ing. Univ. Zulia, 2016)
This article determines the hydrometeorological network interconnectivity in the province of Chim- borazo-Ecuador, a high mountain andean-area and with an irregular landscape, analyzing the technical characteristics of data transmission and data reception via GPRS, GOES and radio links in 802.11. Using the technical field study to outline the best route to connect meteorological and hydrological stations, which will send real-time data. The result is that 24 stations can use GPRS whereas 11 stations must use GOES satellite transmission and 2 stations can use radio links in 802.11b. In conclusion, the radiolinks in 802.11b ful fill a 60% fresnel clearance and an adequate reception level. The average GPRS-GSM reception signal level is ”“76 dBm, being acceptable for real-time transmission.